Elementary French immersion Français : An introduction to the effective use of the Horizon pancanadien collection-Portes ouvertes sur notre pays (Guerin) - Newfoundland and Labrador. Department of Education. Division of Program Development. (Government of Newfoundland and Labrador, Department of Education, Division of Program Development, 1994)
1994_Elementary French Immersion_Francais